A pain assessment method and system - Hughes, Jeff; Hoti, Kreshnik; Atee, Mustafa (2017)
The present disclosure provides a method for determining an effect of a drug on pain experienced by a patient. The method comprises providing reference information concerning at least one visible and/or audible feature that is indicative of a level of the pain. The method further comprises capturing information indicative of the at least one visible and/or audible feature, respectively, from the patient comprising observing the patient directly or indirectly after administering the drug to the patient. In addition, the method comprises determining pain indicating information associated with a level of pain experienced by the patient using the captured information. The method also comprises comparing the pain indicating information with the provided reference information to determine the effect of the drug on the pain experienced by the patient.